Perspectives on positive political economy - Alt, James E.; Shepsle, Kenneth A. (Political economy of institutions and decisions, 1990)
This volume serves as an introduction to the field of positive political economy and the economic and political processes with which it is concerned. This new research tradition is distinct from both normative and historical approaches to political economy. Grounded in the rational-actor methodology of microeconomics, positive political economy is the study of rational decisions in a context of political and economic institutions. More analytical than traditional approaches, it is concerned with the derivation of principles and propositions against which real-world experience may be compared. Its focus is on empirical regularities, and its goal is theoretical explanation. The field has focused on three main areas of research: models of collective action, constraints on competitive market processes, and the analysis of transaction costs. Developments in all of these areas are covered in the book. The first part of the volume surveys the field, while the second part displays positive political economy at work, examining a variety of subjects. The final part contains essays by leading political economists on the theoretical foundations of the field